Automated Peptide Synthesizers and Glycoprotein Synthesis - Tian, Jiekang; Li, Yaohao; Ma, Bo; Tan, Zhongping; Shang, Shiying (Frontiers in Chemistry, 2022)
The development and application of commercially available automated peptide synthesizers has played an essential role in almost all areas of peptide and protein research. Recent advances in peptide synthesis method and solid-phase chemistry provide new opportunities for optimizing synthetic efficiency of peptide synthesizers. The efforts in this direction have led to the successful preparation of peptides up to more than 150 amino acid residues in length. Such success is particularly useful for addressing the challenges associated with the chemical synthesis of glycoproteins. The purpose of this review is to provide a brief overview of the evolution of peptide synthesizer and glycoprotein synthesis. The discussions in this article include the principles underlying the representative synthesizers, the strengths and weaknesses of different synthesizers in light of their principles, and how to further improve the applicability of peptide synthesizers in glycoprotein synthesis.